The uprising of the fedayeen against the government of Jordan, 1970-1971: declassified documents from The British Archive - Muhamad Hasrul Zakariah (Institut Kajian Rantau Asia Barat, 2010)
The defeated of the Arabs in the 1967’s war to the Israeli had created instability and political discord in the Palestinian neighbour countries, particularly the Kingdom of Jordan in 1970s. During the war, a huge number of the new Palestinian refugees or displaced people (DPs) were influxes into the country. The Palestinian refugees who scattered in the refugee camps around Jordan soil than formed a radical militia movement of the fedayeen to fight against the Israeli occupation. As a consequence, Israel retaliation placed Amman in continuous instability and danger. After the war, King Hussein was also lost his popularity among Palestinians, Jordan citizens and the Jordanian army. With a support from the Palestinian refugees, who formed the majority population in many Jordan towns, as well as the Jordanian sympathizers, the fedayeen movement gains their popularity and eventually emerged as a serious political threat to the King rulership. This paper will analyse the conflict from a historical perspective and methodology, based on archival documents sources found at the National Archive of England in London.